2017
DOI: 10.1104/pp.16.01576
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Deficiency Compromises Alternative Pathways of Respiration following Energy Deprivation in Arabidopsis thaliana

Abstract: Under heterotrophic conditions, carbohydrate oxidation inside the mitochondrion is the primary energy source for cellular metabolism. However, during energy-limited conditions, alternative substrates are required to support respiration. Amino acid oxidation in plant cells plays a key role in this by generating electrons that can be transferred to the mitochondrial electron transport chain via the electron transfer flavoprotein/ubiquinone oxidoreductase system. Autophagy, a catabolic mechanism for macromolecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
110
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 78 publications
19
110
1
Order By: Relevance
“…Nutrient starvation induces the formation of autophagosomes to engulf the denatured proteins and transfer them to vacuoles for reuse, leading to enhanced N-utilization efficiency. However, autophagy-defective mutants compromise the degradation of proteins and the generation of amino acids (Barros et al, 2017). Similarly, BR treatment increased N uptake, which was associated with increased activity of nitrate reductase and increased levels of free amino acids and soluble proteins (Dalio et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient starvation induces the formation of autophagosomes to engulf the denatured proteins and transfer them to vacuoles for reuse, leading to enhanced N-utilization efficiency. However, autophagy-defective mutants compromise the degradation of proteins and the generation of amino acids (Barros et al, 2017). Similarly, BR treatment increased N uptake, which was associated with increased activity of nitrate reductase and increased levels of free amino acids and soluble proteins (Dalio et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is functional at basal levels in virtually all cell types under favorable growth conditions but can also be massively induced by a wide array of developmental and environmental stimuli including nutrient starvation, senescence, pathogens, metabolic stress, and many other abiotic and biotic cues (Levine and Kroemer, 2008;Jaishy and Abel, 2016;Anding and Baehrecke, 2017;Wang et al, 2017;Nakamura and Yoshimori, 2018). The functional importance of both inducible and basal autophagy is well illustrated in plants using autophagy-defective mutants of Arabidopsis (Arabidopsis thaliana) and other plants (Liu et al, 2005;Guiboileau et al, 2012;Yoshimoto, 2012;Minina et al, 2014;Yang and Bassham, 2015;Barros et al, 2017;Üstün et al, 2017;Wang et al, 2017Wang et al, , 2018Elander et al, 2018;Enrique Gomez et al, 2018). These mutants display early senescence, shortened lifespan, reduced seed yield, defective reproductive growth, and altered phytohormone signaling under normal growth conditions and are also hypersensitive to nutrient deprivation, oxidative stress, pathogen infection, drought, and high salinity, although many mechanistic details underlying these phenotypes and the stress sensitivity remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Another study using a different set of autophagy-deficient mutants, atg5, atg7 and atg9, showed a lower increase in the levels of basic AAs, aromatic AAs and BCAAs in the atg plants than in wild-type plants during dark treatment. 15 These findings suggest a vital role for autophagy in the production of free AAs in response to sugar shortage.…”
mentioning
confidence: 95%
“…In autophagy-deficient mutants, this response is impaired, resulting in an uncontrolled chloroplast degradation such as the strong activation of chloroplast vesiculation-containing vesicles (CCVs)-mediated pathway, 22 which is independent of autophagy, as previously suggested. 15 e1552057-2 chloroplast stroma-targeted autophagy during such stress conditions to better understand the survival strategies of plants. Numerous studies suggested the importance of autophagy in plant responses to various abiotic stresses, as well overviewed in a recent review.…”
mentioning
confidence: 99%